LIBRARIANISM IN SURKHANDARYA AT THE END OF THE 20TH CENTURY (The Journal of Interdisciplinary Human Studies, 2026)
After our country gained independence, the library sector, like other sectors, experienced many difficulties. In particular, these difficulties did not bypass the libraries of Surkhandarya region. However, thanks to the efforts of dedicated employees, the sector did not lose its place in the life of the state and society.
Keywords: book; communist ideology; reading; library work; culture; economic; problems; book exhibition; conference; library fund